A Bibliometric Analysis of the Current Trends in Collaboration Skills in the Learning Process - ‎ , Misbah; Arlinda, Rossy; Umar, Fadilah; Muhammad, Nurlaela; ‎ , Qamariah; Harto, Muhdi (KnE Social Sciences, 2024)
This study aims to analyze research trends related to collaboration skills in the learning process from 2019 to 2023 through bibliometric analysis with the Scopus database. Based on the criteria, 740 articles from 3176 documents were obtained. The articles have been analyzed from Scopus-indexed international journals. The selected references were supervised utilizing Mendeley, a reference management software. Once it was processed, this study classified and visualized the data using VOSviewer software. The results indicate that research on collaboration skills in the learning process is gradually increasing every year. The United States accounts for the most research globally, followed by Indonesia in fourth place. Four clusters were found while visualizing the research trend of collaboration skills in the learning process from 2019 to 2023. The results of this study offer guidance to future researchers and support them in their research of global trends in the study of collaboration skills in the learning process. Overall, this review serves as a good foundation for subsequent research concerning collaboration skills in the learning process. Keywords: bibliometric analysis, collaboration skills, learning proses